HP1330 Contributes to Streptococcus suis Virulence by Inducing Toll-Like Receptor 2- and ERK1/2-Dependent Pro-inflammatory Responses and Influencing In Vivo S. suis Loads - Zhang, Qiang; Huang, Jingjing; Yu, Junping; Xu, Zhongmin; Liu, Liang; Song, Yajing; Sun, Xiaomei; Zhang, Anding; Jin, Meilin (Frontiers in Immunology, 2017)
Streptococcus suis 2 (SS2) has evolved into a highly invasive pathogen responsible for two large-scale outbreaks of streptococcal toxic shock-like syndrome (STSLS) in China. Excessive inﬂammation stimulated by SS2 is considered a hallmark of STSLS, even it also plays important roles in other clinical symptoms of SS2-related disease, including meningitis, septicemia, and sudden death. However, the mechanism of SS2-caused excessive inﬂammation remains poorly understood. Here, a novel pro-inﬂammatory protein was identified (HP1330), which could induce robust expression of pro-inﬂammatory cytokines (TNF-α, MCP-1, and IL-1β) in RAW264.7 macrophages. To evaluate the role of HP1330 in SS2 virulence, an hp1330-deletion mutant (Δhp1330) was constructed. In vitro, hp1330 disruption led to a decreased pro-inﬂammatory ability of SS2 in RAW 264.7 macrophages. In vivo, Δhp1330 showed reduced lethality, pro-inﬂammatory activity, and bacterial loads in mice. To further elucidate the mechanism of HP1330-induced pro-inﬂammatory cytokine production, antibody blocking and gene-deletion experiments with macrophages were performed. The results revealed that the pro-inﬂammatory activity of HP1330 depended on the recognition of Toll-like receptor 2 (TLR2). Furthermore, a speciﬁc inhibitor of the extracellular signal-regulated kinase 1/2 (ERK1/2) pathways could signiﬁcantly decrease HP1330-induced pro-inﬂammatory cytokine production, and western blot analysis showed that HP1330 could induce activation of the ERK1/2 pathway. Taken together, our findings demonstrate that HP1330 contributes to SS2 virulence by inducing TLR2- and ERK1/2-dependent pro-inﬂammatory cytokine production and influencing in vivo bacterial loads, implying that HP1330 may be associated with STSLS caused by SS2.